Nucleic acids research - Oxford University Press (Oxford University Press, 1974)
Contains current and back issues of the journal, with full electronic delivery up to two weeks ahead of print; full text of articles, 1996-; tables of contents and abstracts only, 1975-1995.
Keywords: Nucleic acids : Periodicals; Nucleic acids; Nucleic Acids; Acides nucléiques; Nucleinsäuren; Zeitschrift; Online-Ressource; Molekulargenetik; Acide nucléique; Séquençage; Génome; Génomique; Biologie structurale; Bio-informatique; Biologie moléculaire; Protéine; Nucleinsäuren; Zeitschrift; Online-Publikation; Molekulargenetik